"Losing our Inuttitut": The intersection of language shift and language attitudes in Nain, Nunatsiavut - Thorburn, Jennifer (2018)
This chapter examines the relationship between language shift and language attitudes, with the Canadian Inuit community of Nain, Nunatsiavut, serving as a case study. This remote town is currently undergoing the later stages of language shift: the indigenous language, Inuktitut (or Inuttitut, as the Labrador varieties are known), is being replaced by English as the primary means of communication and socialisation within the community. In Nain, this shift began within living memory, starting in the 1950s, and dividing the community along linguistic lines: elders are largely monolingual speakers of Inuttitut, and younger residents speak predominantly English, with minimal knowledge of their ancestral language. Residents demonstrate strong metalinguistic awareness in interviews, frequently discussing how the two languages – Inuttitut and English – are regarded and used in Nain, and how the shift to English has impacted not only linguistic practices in the community but also residents' sense of culture and identity. Particular focus is placed on how the provincial government's institution of English as the language of education in the 1950s and the subsequent evolution of the educational system have impacted perceptions and use of both community languages, as provincially mandated schooling is the factor most commonly mentioned by residents when discussing the loss of Inuttitut in Nunatsiavut.